I'M A FUTURE ASTRONOMER! - Nayak, Manisha; Ong, Eliz (Singapore : WS Education, 2022)
Why do stars twinkle? Why is Pluto no longer considered a planet? Who was the first animal in space? Is a day on Venus really longer than a year on Venus? What really is a shooting star? Curious to find out the answers to these questions? Join Astro the asteroid on an exciting journey and learn all about space. The I'm a Future Scientist! series is based on the Science Centre Singapore's longstanding and highly popular Young Scientist badge programme. This exciting series of full-colour books for 6-12 year olds will spark sustained interest in scientific fields, such as botany, zoology, marine biology, conservation and the environment, astronomy, and many more, with delivering primary-school-level Science learning points in an engaging and relatable way! Through clearly written educational articles, fun cartoons, suggested hands-on activities, as well as full-colour photographs and illustrations, these books are the perfect companions for budding scientists to delve further into a wide range of fields of Science. In addition, Augmented Reality (AR) elements will also help to bring Science alive for children, helping them to retain the information provided better, and inspiring better learning! And, as a bonus, earn points for the Young Scientist Badge programme from Science Centre Singapore, using the links inside! SERIES DISTINCTIVES
Keywords: Astronomer -- Juvenile literature; Astronomy -- Juvenile literature